2022
DOI: 10.1021/acsaem.2c01964
|View full text |Cite
|
Sign up to set email alerts
|

2D CoFe-LDH Nanosheet-Incorporated 1D Microfibers as a High-Performance OER Electrocatalyst in Neutral and Alkaline Media

Abstract: Compositional-variation-induced CoFe-LDHs (with various Co:Fe ratio; LDH, layered double hydroxide) have been prepared via a simple wet-chemical method followed by the formation of 1D microfibers through electrospinning (ES) techniques. The as-synthesized 1D fiber with a Co/Fe ratio corresponding to a 0.5:1 microfiber (CoFe-LDH 0.5 fiber) showed the highest oxygen evolution reaction (OER) activity by demanding an overpotential value of 267 mV while the corresponding powder material demands an overpotential val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 49 publications
(83 reference statements)
1
29
0
Order By: Relevance
“…Based on ECSA-normalized LSV curves (Figure b,c), unsurprisingly, Co-MOF/Fe 10 shows the lowest overpotential at the given current density, suggesting its higher inherent OER activity than FeOOH and Co-MOF/Fe n ( n = 0, 5, 20, 30). Thus, the exceptional OER activity of Co-MOF/Fe 10 not only stems from its large ECSAs but is also closely related to its high inherent OER activity, which is thought to arise from the bimetallic synergistic effect between Co and Fe. ,, It can be demonstrated that the Fe doping strategy is able to improve the performance of the OER by all the above electrochemical data analysis.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on ECSA-normalized LSV curves (Figure b,c), unsurprisingly, Co-MOF/Fe 10 shows the lowest overpotential at the given current density, suggesting its higher inherent OER activity than FeOOH and Co-MOF/Fe n ( n = 0, 5, 20, 30). Thus, the exceptional OER activity of Co-MOF/Fe 10 not only stems from its large ECSAs but is also closely related to its high inherent OER activity, which is thought to arise from the bimetallic synergistic effect between Co and Fe. ,, It can be demonstrated that the Fe doping strategy is able to improve the performance of the OER by all the above electrochemical data analysis.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, the exceptional OER activity of Co-MOF/Fe 10 not only stems from its large ECSAs but is also closely related to its high inherent OER activity, which is thought to arise from the bimetallic synergistic effect between Co and Fe. 43,47,48 It can be demonstrated that the Fe doping strategy is able to improve the performance of the OER by all the above electrochemical data analysis.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%
“…S7 †), are ascribed to O-H stretching vibration, H-O-H stretching vibration, adsorbed water molecules, the antisymmetric stretching vibration of carbonate species and the P-O-P stretching vibration, while the absorption band at a lower wavenumber below 800 cm −1 is mainly ascribed to metal-oxygen stretching and bending vibrations, which are related to a brucite-like structure. 25,[31][32][33][34] Moreover, the CoFe-LDH@NiCoP/NF has a surface area of 6.7 m 2 g −1 and a pore size of 15.34 nm. However, the surface area of CoFe-LDH/NF and NiCoP/NF is only 2.03 and 1.61 m 2 g −1 , respectively.…”
Section: Composition and Morphology Analysismentioning
confidence: 99%
“…Water electrolysis toward oxygen and hydrogen production is being improved as a possible strategy to store renewable energy when the wind or sun is unavailable. A limitation of water electrolysis is the oxygen evolution reaction (OER), which provides the electrons for a water reduction reaction. However, OER is a sluggish and complicated reaction. Recently, Ni complexes have been extensively applied as OER (pre)­catalysts.…”
Section: Introductionmentioning
confidence: 99%